Independence, institutionalization, death and treatment costs 18 months after rehabilitation of older people in two different primary health care settings - Johansen Inger; Lindbak Morten; Stanghelle Johan K; Brekke Mette (BMC, 2012)
Abstract Background The optimal setting and content of primary health care rehabilitation of older people is not known. Our aim was to study independence, institutionalization, death and treatment costs 18 months after primary care rehabilitation of older people in two different settings. Methods Eighteen months follow-up of an open, prospective study comparing the outcome of multi-disciplinary rehabilitation of older people, in a structured and intensive Primary care dedicated inpatient rehabilitation (PCDIR, n=202) versus a less structured and less intensive Primary care nursing home rehabilitation (PCNHR, n=100). Participants: 302 patients, disabled from stroke, hip-fracture, osteoarthritis and other chronic diseases, aged ≥65years, assessed to have a rehabilitation potential and being referred from general hospital or own residence. Outcome measures: Primary: Independence, assessed by Sunnaas ADL Index(SI). Secondary: Hospital and short-term nursing home length of stay (LOS); institutionalization, measured by institutional residence rate; death; and costs of rehabilitation and care. Statistical tests: T-tests, Correlation tests, Pearson's χ2, ANCOVA, Regression and Kaplan-Meier analyses. Results Overall SI scores were 26.1 (SD 7.2) compared to 27.0 (SD 5.7) at the end of rehabilitation, a statistically, but not clinically significant reduction (p=0.003 95%CI(0.3-1.5)). The PCDIR patients scored 2.2points higher in SI than the PCNHR patients, adjusted for age, gender, baseline MMSE and SI scores (p=0.003, 95%CI(0.8-3.7)). Out of 49 patients staying >28 days in short-term nursing homes, PCNHR-patients stayed significantly longer than PCDIR-patients (mean difference 104.9 days, 95%CI(0.28-209.6), p=0.05). The institutionalization increased in PCNHR (from 12%-28%, p=0.001), but not in PCDIR (from 16.9%-19.3%, p= 0.45). The overall one year mortality rate was 9.6%. Average costs were substantially higher for PCNHR versus PCDIR. The difference per patient was 3528€ for rehabilitation (p<0.001, 95%CI(2455-4756)), and 10134€ for the at-home care (p=0.002, 95%CI(4066-16202)). The total costs of rehabilitation and care were 18702€ (=1.6 times) higher for PCNHR than for PCDIR. Conclusions At 18 months follow-up the PCDIR-patients maintained higher levels of independence, spent fewer days in short-term nursing homes, and did not increase the institutionalization compared to PCNHR. The costs of rehabilitation and care were substantially lower for PCDIR. More communities should consider adopting the PCDIR model. Trial registration Clinicaltrials.gov ID NCT01457300